Preparation method of high-density recrystallized silicon carbide
By using the mixing and kneading and extrusion molding process of silicon carbide powder and additives in recrystallized sintered silicon carbide materials with different particle sizes, combined with the pressure-free sintering process, the density and mechanical properties of the material are successfully improved, and the porosity of the existing materials is solved. High and low density problems.
Patent Information
- Application Number
- CN202411650364.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The existing recrystallized sintered silicon carbide materials have high porosity and low density, resulting in poor mechanical properties, limiting their application in certain fields.
By fully mixing silicon carbide powder, additives and solvents of different particle sizes in the mixer, uniform mud is formed, and then formed in a kneading and extrusion machine, and high-temperature sintering is carried out in a recrystallization sintering furnace. Pressure sintering process to prepare high-density recrystallized silicon carbide.
It significantly improves the density and crystallization quality of recrystallized silicon carbide, improves its hardness, wear resistance and high temperature stability, and expands its application potential in extreme environments.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon carbide material preparation, and in particular to a method for preparing high-density recrystallized silicon carbide. Background Art
[0002] Silicon carbide (SiC), as an important non-oxide ceramic material, has broad application prospects in aerospace, energy, chemical industry, electronics and other fields due to its unique physical and chemical properties, such as high hardness, high melting point, excellent corrosion resistance, high thermal conductivity and good thermal shock resistance. With the advancement of science and technology and the development of industry, the demand for high-performance silicon carbide materials is growing, especially the demand for high-density recrystallized silicon carbide is particularly urgent.
[0003] Although the reaction sintering process is simple, the product often contains more free silicon, which affects the performance. Although the existing recrystallized silicon carbide (R-SiC) has many excellent properties, such as high hardness, high melting point, excellent corrosion resistance, high thermal conductivity and good thermal shock resistance, it still has some defects in practical applications. The main reason is that the traditional recrystallized sintered silicon carbide has high porosity and low density, which limits its progress in replacing reaction sintered silicon carbide and its application in certain fields. Therefore, it is particularly important to develop a method for preparing recrystallized silicon carbide that can both ensure high density and improve its microstructure to enhance the mechanical properties of the material. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing high-density recrystallized silicon carbide, so as to solve the problems of high porosity, low density and poor mechanical properties of recrystallized sintered silicon carbide in the existing method.
[0005] The scheme of the present invention is:
[0006] A method for preparing high-density recrystallized silicon carbide, characterized in that it comprises the following steps:
[0007] 1) Putting silicon carbide powder of different particle sizes, additives, and solvents into a mixer, and mixing them thoroughly to obtain a slurry for preparing high-density recrystallized silicon carbide; the additives include a plasticizer, a binder, a pH regulator, and a sintering aid, which are added in sequence;
[0008] 2) Put the clay into a kneading and extruding machine for kneading and molding;
[0009] 3) The formed clay material is dried to obtain a dry blank for preparing high-density recrystallized silicon carbide;
[0010] 4) The dry blank is placed in a recrystallization sintering furnace, and high-density recrystallized silicon carbide products are obtained after high-temperature sintering according to the sintering curve and sintering atmosphere.
[0011] As a preferred technical solution, the silicon carbide powder in step 1) includes silicon carbide powder a with a D50 of 698.01 μm, silicon carbide powder b with a D50 of 101.21 μm, and silicon carbide powder c with a D50 of 12.50 μm; the mass ratio of the silicon carbide powder a, silicon carbide powder b, and silicon carbide powder c is 2:4:3~4.
[0012] As a preferred technical solution, the plasticizer is one of methyl cellulose, carboxymethyl cellulose, sodium methyl cellulose and sodium carboxymethyl cellulose, and the added amount is 1% to 5% of the weight of the silicon carbide powder.
[0013] As a preferred technical solution, the binder is two of polyvinyl alcohol, PVPK60, polyethylene glycol 4000, polypropylene, and phenolic resin, and the added amount is 1% to 5% of the weight of silicon carbide powder. The mass ratio of the two binders is 1:1 to 5.
[0014] As a preferred technical solution, the pH regulator is one of sodium tripolyphosphate, acrylamide and polyacrylamide, and the added amount is 0.3% to 1% of the weight of the silicon carbide powder.
[0015] As a preferred technical solution, the sintering aid is one of Al2O3, Y2O3, and B4C, with a particle size distribution of 20 to 100 nm, and an added amount of 0.5% to 0.8% of the weight of the silicon carbide powder.
[0016] As a preferred technical solution, the solvent in step 1) is two of deionized water, tetraethyl orthosilicate, water glass, and trimethylsilanol, and the added amount is 10% to 16% of the weight of the silicon carbide powder, and the mass ratio of the two solvents is 1:0.5 to 3.
[0017] As a preferred technical solution, the mixing time in step 1) is 4 to 8 hours, and the moisture content of the mud after mixing is 8.2% to 15.3%; the moisture content of the mud after molding in step 2) is 5.1 to 8.2%.
[0018] As a preferred technical solution, the drying process in the step 3) is divided into shade drying and oven drying processes, wherein the temperature of the shade drying process is 15°C to 45°C, the time is 12 to 120 hours, and the relative humidity is 25% to 50%; the temperature of the oven drying process is 50°C to 80°C, the time is 12 to 48 hours, and the relative humidity is 25% to 50%.
[0019] As a preferred technical solution, the sintering atmosphere in the step 4) is one of Ar, N2, CO2, He, and CH4, and the gas flow rate is 55 to 210 L / min; the sintering curve is specifically as follows: keeping warm at a temperature of 450°C to 810°C for 240 to 600 min; keeping warm at a temperature of 1320°C to 1500°C for 240 to 600 min; keeping warm at a temperature of 1900°C to 2200°C for 240 to 480 min; keeping warm at a temperature of 2300°C to 2400°C for 180 to 300 min.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention uses silicon carbide powder of different particle sizes, adds plasticizer, binder, pH regulator, sintering aid, and solvent in sequence, mixes them evenly, forms them by extrusion, and then couples the recrystallization sintering process with the pressureless sintering process in situ to prepare high-density recrystallized silicon carbide products, aiming to improve the density and mechanical properties of recrystallized sintered silicon carbide ceramics to meet high-end application requirements. Due to the coupling of the pressureless sintering process in the recrystallization process, the density of the recrystallized silicon carbide prepared by the present invention reaches 2.71g / cm 3 , porosity is 14.8%, three-point bending strength is 105MPa, and it has good density and mechanical strength.
[0022] 2. The high-density recrystallized silicon carbide preparation method of the present invention significantly improves the density and crystal quality of silicon carbide materials through optimized process parameters and innovative preparation processes. This high-density recrystallized silicon carbide has higher hardness and wear resistance, and exhibits better stability and corrosion resistance at high temperatures, greatly expanding the application potential of silicon carbide materials in extreme environments. DETAILED DESCRIPTION
[0023] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0024] The specifications of the silicon carbide powder in the present invention are as follows:
[0025] name D10(μm) D50(μm) D90(μm) Powder a 688.89 698.01 712.53 Powder b 89.96 101.21 110.75 Powder c 7.64 12.50 18.67
[0026] Embodiment 1:
[0027] Weigh 2000g of powder a, 4000g of powder b, and 4000g of powder c, put them into a mixer and stir for 30 minutes at 25°C. Add 100g of methyl cellulose, continue stirring for 30 minutes, add 120g of polyvinyl alcohol PVA and 240g of PVP K60, stir for 5 minutes, add 30g of sodium tripolyphosphate, stir for 20 minutes, add 50g of B4C, stir for 10 minutes, add 666.6g of deionized water and 333.4g of tetraethyl orthosilicate TEOS, continue stirring for 360 minutes, then take out the material. After mixing, the moisture content of the mud is 8.2%.
[0028] The clay was kneaded in a kneading and extruding machine for 4 hours and then extruded into shape. The temperature during the kneading and extruding process was 20°C and the vacuum degree was -0.12MPa. The upper shaft frequency of the extruder was 30Hz, and the lower shaft frequency was 50Hz. The moisture content of the clay after molding was 5.1%.
[0029] Dry in the shade at 20°C and 35% relative humidity for 48 hours, then dry in an oven at 65°C and 24% relative humidity for 24 hours.
[0030] The obtained dry blank is placed in a recrystallization sintering furnace and sintered under argon gas with a gas flow rate of 55L / min. It is first kept at 600°C for 240min, then kept at 1320°C for 240min, then kept at 2000°C for 260min, and finally kept at 2350°C for 180min. After sintering, high-density recrystallized silicon carbide is obtained.
[0031] After testing, the density of the recrystallized silicon carbide is 2.58g / cm 3 , porosity is 22.1%, and three-point bending strength reaches 105MPa.
[0032] Embodiment 2:
[0033] Adjust the particle size distribution, weigh 1300g powder a, 6700g powder b, 3000g powder c, put them into the mixer and stir at room temperature for 45min. Add 100g methyl cellulose, continue stirring for 30min, add 120g polyvinyl alcohol PVA and 360g PVPK60, stir for 15min, add 100g sodium tripolyphosphate, stir for 25min, add 80g B4C with a particle size distribution of 20-100nm, stir for 25min, add 100g deionized water and 500g tetraethyl orthosilicate TEOS, continue stirring for 360min and take out the material. After mixing, the moisture content of the mud is 12.0%.
[0034] The clay was kneaded in a kneading and extruding machine for 4 hours and then extruded into shape. The temperature during the kneading and extruding process was 20°C and the vacuum degree was -0.12MPa. The upper shaft frequency of the extruder was 30Hz and the lower shaft frequency was 50Hz. The moisture content of the clay after molding was 7.2%.
[0035] Dry in the shade at 20°C and 35% relative humidity for 48 hours, then dry in an oven at 65°C and 24% relative humidity for 48 hours.
[0036] The obtained dry blank is placed in a recrystallization sintering furnace and sintered under argon gas with a gas flow rate of 75L / min. It is first kept at 600°C for 240min, then kept at 1320°C for 240min, then kept at 2000°C for 260min, and finally kept at 2350°C for 180min. After sintering, high-density recrystallized silicon carbide is obtained.
[0037] After testing, the density of the recrystallized silicon carbide is 2.71g / cm 3 , porosity is 14.8%, and three-point bending strength reaches 150MPa.
[0038] Embodiment 3:
[0039] Use Al2O3 as sintering aid and adjust the type of sintering aid. Weigh 2000g powder a, 4000g powder b, 4000g powder c, put into a mixer and stir for 30min at 25℃. Add 100g carboxymethyl cellulose, continue stirring for 30min, add 120g polyvinyl alcohol PVA and 240g polyethylene glycol 4000 (PEG 4000), stir for 5min, add 30g acrylamide, stir for 20min, add 50g Al2O3, stir for 10min, add 666.6g deionized water and 333.4g tetraethyl orthosilicate TEOS, continue stirring for 360min and take out the material. After mixing, the moisture content of the mud is 10.1%.
[0040] The clay was kneaded in a kneading and extruding machine for 4 hours and then extruded into shape. The temperature during the kneading and extruding process was 20°C and the vacuum degree was -0.12MPa. The upper shaft frequency of the extruder was 30Hz, and the lower shaft frequency was 50Hz. The moisture content of the clay after molding was 6.3%.
[0041] Dry in the shade at 20°C and 35% relative humidity for 48 hours, then dry in an oven at 65°C and 24% relative humidity for 24 hours.
[0042] The obtained dry blank is placed in a recrystallization sintering furnace and sintered under argon gas with a gas flow rate of 55L / min. It is first kept at 600°C for 240min, then kept at 1320°C for 240min, then kept at 2000°C for 260min, and finally kept at 2350°C for 180min. After sintering, high-density recrystallized silicon carbide is obtained.
[0043] After testing, the density of the recrystallized silicon carbide is 2.63g / cm 3 , porosity is 17.2%, and three-point bending strength reaches 135MPa.
[0044] Embodiment 4:
[0045] Adjust the amount of sintering aid. Weigh 1300g of powder a, 6700g of powder b, and 3000g of powder c, put them into a mixer and stir at room temperature for 45 minutes. Add 100g of methyl cellulose, continue stirring for 30 minutes, add 120g of polyvinyl alcohol PVA and 360g of PVPK60, stir for 15 minutes, add 100g of sodium tripolyphosphate, stir for 25 minutes, add 100g of B4C with a particle size distribution of 20-100nm, stir for 25 minutes, add 100g of deionized water and 500g of tetraethyl orthosilicate TEOS, continue stirring for 360 minutes and take out the material. After mixing, the moisture content of the mud is 11.3%.
[0046] The clay was kneaded in a kneading and extruding machine for 4 hours and then extruded into shape. The temperature during the kneading and extruding process was 20°C and the vacuum degree was -0.12MPa. The upper shaft frequency of the extruder was 30Hz, the lower shaft frequency was 50Hz, and the moisture content of the clay after molding was 5.5%.
[0047] Dry in the shade at 20°C and 35% relative humidity for 48 hours, then dry in an oven at 65°C and 24% relative humidity for 24 hours.
[0048] The obtained dry blank is placed in a recrystallization sintering furnace and sintered under argon gas with a gas flow rate of 55L / min. It is first kept at 600°C for 240min, then kept at 1320°C for 240min, then kept at 2000°C for 260min, and finally kept at 2350°C for 180min. After sintering, high-density recrystallized silicon carbide is obtained.
[0049] After testing, the density of the recrystallized silicon carbide is 2.69g / cm 3 , porosity is 15.6%, and three-point bending strength reaches 139MPa.
[0050] Embodiment 5:
[0051] Use Y2O3 as sintering aid, adjust the type of sintering aid, and change the silicon source. Weigh 2000g powder a, 4000g powder b, and 4000g powder c, put them into a mixer and stir at 25°C for 30 minutes. Add 300g sodium methyl cellulose, continue stirring for 30 minutes, add 120g phenolic resin and 240g polypropylene, stir for 5 minutes, add 100g polyacrylamide, stir for 20 minutes, add 50g Y2O3, stir for 10 minutes, add 666.6g deionized water and 333.4g water glass, continue stirring for 360 minutes, and then take out the material. After mixing, the moisture content of the mud is 12.8%.
[0052] The clay was kneaded in a kneading and extruding machine for 4 hours and then extruded into shape. The temperature during the kneading and extruding process was 20°C and the vacuum degree was -0.12MPa. The upper shaft frequency of the extruder was 30Hz, and the lower shaft frequency was 50Hz. The moisture content of the clay after molding was 8.5%.
[0053] Dry in the shade at 20°C and 35% relative humidity for 48 hours, then dry in an oven at 65°C and 24% relative humidity for 24 hours.
[0054] The obtained dry blank is placed in a recrystallization sintering furnace and sintered under argon gas with a gas flow rate of 55L / min. It is first kept at 600°C for 240min, then kept at 1320°C for 240min, then kept at 2000°C for 260min, and finally kept at 2350°C for 180min. After sintering, high-density recrystallized silicon carbide is obtained.
[0055] After testing, the density of the recrystallized silicon carbide is 2.60g / cm 3 , porosity is 19% and three-point bending strength reaches 130MPa.
[0056] Embodiment 6:
[0057] Adjust the amount of sintering aid and change the silicon source. Weigh 2000g of powder a, 4000g of powder b, and 4000g of powder c, put them into a mixer and stir at 25°C for 30 minutes. Add 300g of sodium carboxymethyl cellulose, continue stirring for 30 minutes, add 100g of polyvinyl alcohol PVA and 300g of polypropylene, stir for 5 minutes, add 30g of sodium tripolyphosphate, stir for 20 minutes, add 50g of B4C, stir for 10 minutes, add 900g of deionized water and 333g of trimethylsilanol, continue stirring for 360 minutes and take out the material. After mixing, the moisture content of the mud is 11.9%.
[0058] The clay was kneaded in a kneading and extruding integrated machine for 4 hours and then extruded into shape. The temperature during the kneading and extruding process was 20°C and the vacuum degree was -0.12MPa. The upper shaft frequency of the extruder was 30Hz and the lower shaft frequency was 50Hz. The moisture content of the clay after molding was 7.5%.
[0059] Dry in the shade at 20°C and 35% relative humidity for 48 hours, then dry in an oven at 65°C and 24% relative humidity for 24 hours.
[0060] The obtained dry blank is placed in a recrystallization sintering furnace and sintered under argon gas with a gas flow rate of 55L / min. It is first kept at 600°C for 240min, then kept at 1320°C for 240min, then kept at 2000°C for 260min, and finally kept at 2350°C for 180min. After sintering, high-density recrystallized silicon carbide is obtained.
[0061] After testing, the density of the recrystallized silicon carbide is 2.60g / cm 3 , porosity is 19.3% and three-point bending strength reaches 128MPa.
[0062] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing high-density recrystallized silicon carbide, characterized in that: The following steps are involved: 1) Putting silicon carbide powder of different particle sizes, additives, and solvents into a mixer, and mixing them thoroughly to obtain a slurry for preparing high-density recrystallized silicon carbide; the additives include a plasticizer, a binder, a pH regulator, and a sintering aid; 2) Put the clay into a kneading and extruding machine for kneading and molding; 3) The formed clay material is dried to obtain a dry blank for preparing high-density recrystallized silicon carbide; 4) The dry blank is placed in a recrystallization sintering furnace, and high-density recrystallized silicon carbide products are obtained after high-temperature sintering according to the sintering curve and sintering atmosphere.
2. A method for preparing high-density recrystallized silicon carbide according to claim 1, characterized in that: The silicon carbide powder in step 1) includes silicon carbide powder a with a D50 of 698.01 μm, silicon carbide powder b with a D50 of 101.21 μm, and silicon carbide powder c with a D50 of 12.50 μm; the mass ratio of the silicon carbide powder a, silicon carbide powder b, and silicon carbide powder c is 2:4:3-4.
3. The method for preparing high-density recrystallized silicon carbide according to claim 1, characterized in that: The plasticizer is one of methyl cellulose, carboxymethyl cellulose, sodium methyl cellulose and sodium carboxymethyl cellulose, and the added amount is 1% to 5% of the weight of the silicon carbide powder.
4. The method for preparing high-density recrystallized silicon carbide according to claim 1, characterized in that: The binder is two of polyvinyl alcohol, PVPK60, polyethylene glycol 4000, polypropylene and phenolic resin, and the added amount is 1% to 5% of the weight of silicon carbide powder. The mass ratio of the two binders is 1:1 to 5.
5. The method for preparing high-density recrystallized silicon carbide according to claim 1, characterized in that: The pH regulator is one of sodium tripolyphosphate, acrylamide and polyacrylamide, and the added amount is 0.3% to 1% of the weight of the silicon carbide powder.
6. The method for preparing high-density recrystallized silicon carbide according to claim 1, characterized in that: The sintering aid is one of Al2O3, Y2O3 and B4C, with a particle size distribution of 20-100nm and an addition amount of 0.5%-0.8% of the weight of the silicon carbide powder.
7. The method for preparing high-density recrystallized silicon carbide according to claim 1, characterized in that: In the step 1), the solvent is two of deionized water, tetraethyl orthosilicate, water glass and trimethylsilanol, the added amount is 10% to 16% of the weight of the silicon carbide powder, and the mass ratio of the two solvents is 1:0.5 to 3.
8. The method for preparing high-density recrystallized silicon carbide according to claim 1, characterized in that: The mixing time in step 1) is 4 to 8 hours, and the moisture content of the mud after mixing is 8.2% to 15.3%; the moisture content of the mud after molding in step 2) is 5.1 to 8.2%.
9. The method for preparing high-density recrystallized silicon carbide according to claim 1, characterized in that: The drying process in step 3) is divided into shade drying and oven drying, wherein the shade drying process is performed at a temperature of 15°C to 45°C, a time of 12 to 120 hours, and a relative humidity of 25% to 50%; the oven drying process is performed at a temperature of 50°C to 80°C, a time of 12 to 48 hours, and a relative humidity of 25% to 50%.
10. The method for preparing high-density recrystallized silicon carbide according to claim 1, characterized in that: In the step 4), the sintering atmosphere is one of Ar, N2, CO2, He, and CH4, and the gas flow rate is 55 to 210 L / min; the sintering curve is specifically as follows: keeping warm at a temperature of 450°C to 810°C for 240 to 600 min; keeping warm at a temperature of 1320°C to 1500°C for 240 to 600 min; keeping warm at a temperature of 1900°C to 2200°C for 240 to 480 min; keeping warm at a temperature of 2300°C to 2400°C for 180 to 300 min.
Citation Information
Cited By
Glass carbon mold, recrystallized silicon carbide product and preparation method
CN121470957A